Usability Testing of the AIS Mobile Application Using the User Centered Design Method for New Information Systems Students at UIN Syarif Hidayatullah Jakarta: Usability Testing Aplikasi AIS Mobile Menggunakan Metode User Centered Design pada Mahasiswa Baru Sistem Informasi UIN Syarif Hidayatullah Jakarta - Fajar Mauludin, Bintang; Subiyakto, A’ang (Journal of Vocational Education and Information Technology (JVEIT), 2023)
Many individuals all across the world now depend heavily on their smartphones in their daily lives. Building mobile applications gives the chance to connect with a very sizable and growing user base. Mobile applications have a large market potential due to their constantly growing user base. Icons on the phone screen make it simple and quick to access mobile applications. Users don't need to open a browser or type a website address in order to utilize an application; they simply need to click on the application icon. According to the results of the questionnaire given to 21 respondents, UIN Jakarta's AIS Mobile application scored 64.87% on usability. Due to this, the User Centered Design build method was used in this study to build the AIS website for UIN Syarif Hidayatullah Jakarta in order to increase the usability value of the website in the aspects of Learnability, Efficiency, Memorability, Error Prevention, and Satisfication Assessment.